On-Surface Synthesis of Porous Carbon Nanoribbons on Silver: Reaction Kinetics and the Influence of the Surface Structure - Ammon, Maximilian Michael; Haller, Martin; Sorayya, Shadi; Maier, Sabine (ChemPhysChem, 2019)
We report on the influence of the surface structure and the reaction kinetics in the bottom-up fabrication of porous nanoribbons on silver surfaces using low-temperature scanning tunneling microscopy. The porous carbon nanoribbons are fabricated by the polymerization of 1,3,5-tris(3-bromophenyl)benzene directly on the Ag surface using an Ullmann-type reaction in combination with dehydrogenative coupling reactions. We demonstrate the successful on-surface synthesis of porous nanoribbons on Ag(111) and Ag(100) even though the self-assemblies of the intermediate organometallic structures and covalently-linked polymer chains are different on both surfaces. Furthermore, we present the formation of isolated porous nanoribbons by kinetic control. Our results give valuable insights into the role of substrate-induced templating effects and the reaction kinetics in the on-surface synthesis of conformationally flexible molecules.
CRIS-Team Scopus Importer:2019-09-24
Keywords: molecular self-assembly; on-surface reactions; scanning probe microscopy; surface chemistry; Ullmann-type reaction